Spectrophotometric Studies on the Stability Constant of Al3+, In3+ and Ga3+ Chelates with Erichrome Cyanin-R - Garg, Abha; Gupta, K.D.; Saxena, K.K. (Asian Journal of Chemistry, 2010)
The interaction of metal ion (AI3+, In3+ and Ga3+) with Erichrome Cyanin-R (ECR) has been investigated by spectrophotometric technique. Light purple and purple coloured chelate having 1 : 2 metal to ligand ratio are formed over the pH range of 3.5 to 5.5 with λmax 515 nm for ECR, 540 for Al3+, In3+ and 530 nm for Ga3+. Their stability constants have been determined by applying mole ratio method, Job's method of continuous variation and Dey and Coworkerrs' method. The values of log K for AI3+; ln3+ and Ga3+ were found to be 10.05, 7.77 and 8.5 respectively. The analytical applications of the colour reaction have also been investigated.